1997
DOI: 10.2307/1468168
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chemical Characteristics of Autumn-Shed Leaves and Aquatic Processing Rates

Abstract: Processing rates of autumn-shed leaves in aquatic habitats are highly variable. It has been hypothesized that these processing rates may, in part, be regulated by the concentrations of residual tannins in the leaves. Tests of this hypothesis have been inconclusive, and experimental designs may have been compromised by the use of both processing rates and tannin concentrations taken from a variety of sources using highly variable methods, sites, and experimental conditions. Here, processing rates of 48 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
194
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(205 citation statements)
references
References 20 publications
6
194
2
3
Order By: Relevance
“…The decay rates of maple and oak leaves we determined are comparable to those reported from other studies which also found oak leaves to be processed more slowly than maple leaves (47,53). The exponential decay model explained 69 and 61% of the variability for maple and oak leaves, respectively, in our study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The decay rates of maple and oak leaves we determined are comparable to those reported from other studies which also found oak leaves to be processed more slowly than maple leaves (47,53). The exponential decay model explained 69 and 61% of the variability for maple and oak leaves, respectively, in our study.…”
Section: Discussionsupporting
confidence: 89%
“…White oak leaves have a higher lignin content and greater toughness than sugar maple leaves that should require greater microbial action to breakdown (47). Yet, in spite of these differences in decomposition and known differences in leaf chemistry (47), few differences in the microbial community were detected between the leaf species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower enzymatic activities for the biofilm on Platanus x hispanica was already observed in previous studies developed on leaf decomposition in soil and in other aquatic habitats. The high C : N ratio measured in this substratum (Bernal et al 2003, Ostrofsky 1997) may be pointed out as the cause for the low mineralisation observed for this material. Slower breakdown of Platanus leaves than other indigenous Mediterranean leaf species (e. g: Populus nigra) (Casas & Gessner 1999) is probably caused by the higher lignin and other recalcitrant compounds content in the former (Ostrofsky 1997).…”
Section: Discussionmentioning
confidence: 67%